The effect of graphene‐based nanofillers on the structure, thermal, and mechanical properties of poly(vinyl alcohol). Issue 30 (20th May 2022) - Rahbarshendi, Faezeh; Baybordiani, Ayda; Asgharzadeh, Hamed; Badr, Milad; Hassannezhad, Kosar
Abstract: PVA matrix composite films reinforced with graphene oxide (GO) and reduced graphene oxide (rGO) nanoplatelets are prepared by water‐solution processing. The structure and properties of the composites are investigated by field‐emission scanning electron microscopy, Raman spectroscopy, Fourier‐transform infrared spectroscopy, differential scanning calorimetry, and dynamic mechanical analysis. The results indicate a 22% improvement in the storage modulus and a 12°C increase in the glass transition temperature by the addition of only 0.5 wt% rGO into the PVA. The enhancement of the mechanical and thermal properties of the composite films is attributed to the hydrogen bond barrier and molecule movement restriction effects. The higher amount of the hydrogen bonds in the PVA/rGO composite compared to the PVA/GO sample cause its higher thermal stability and mechanical performance. Abstract :